2019
DOI: 10.3390/catal9060533
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Oxide Faceted Structures as a Photocatalyst Produced Using an Atmospheric Pressure Plasma Jet

Abstract: The photocatalyst bismuth oxide, which is active under visual light, was deposited using an atmospheric pressure plasma jet (APPJ). Sixteen different samples were generated under different parameters of the APPJ to investigate their catalytic activity. The prepared samples were characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), laser scanning microscopy (LSM), and UV–vis diffuse reflectance absorption spectroscopy. The measured data, such as average sample thickness, coverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…[ 20 ] The deconvolution of the O1s XPS region (Figure 4g) results in two peaks at 529.8 and 531.3 eV, respectively corresponding to the lattice oxygen and its shifted component due to an oxygen deficiency in the bismuth oxide. [ 20–21 ] In Figure 4h,i, the X‐ray diffraction (XRD) pattern and Raman spectrum of the expelled product reveals an alpha‐phase bismuth oxide (α‐Bi 2 O 3 ). The full indexed XRD pattern is available in Figure S4 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 20 ] The deconvolution of the O1s XPS region (Figure 4g) results in two peaks at 529.8 and 531.3 eV, respectively corresponding to the lattice oxygen and its shifted component due to an oxygen deficiency in the bismuth oxide. [ 20–21 ] In Figure 4h,i, the X‐ray diffraction (XRD) pattern and Raman spectrum of the expelled product reveals an alpha‐phase bismuth oxide (α‐Bi 2 O 3 ). The full indexed XRD pattern is available in Figure S4 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The former peak, corresponding to the lattice oxygen, exhibits a significant shift due to the increasing loss of oxygen (i.e., oxygen deficiency) in the bismuth oxide structure. [ 20–21 ] The peak at 532.2 eV corresponds to the physisorbed water or OH − species in the sample. [ 27 ] The Raman spectrum of the product from the expulsion process in 1.0 m KCl–0.10 m NaOH is presented in Figure 6f.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that the metal oxide was present on the surface of the CSs, the CSs were manufactured in two stages-at first, a polyester layer was sprayed onto the wood samples, afterwards the metal or metal oxide was applied. The parameters used for the coating process refer to the layers described in Köhler et al [7,27] and are shown in Table 1. Before the coating process, the wood samples were conditioned at 20 • C/65% relative humidity (RH) until constant mass was reached, and the densities of European beech and pine sapwood were measured with a balance (Kern KB 360-3N, KERN & Sohn GmbH, Balingen, Germany)-the density is 690.1 kg/m 3 and 514.8 kg/m 3 , respectively.…”
Section: Coating Processmentioning
confidence: 99%